A heat pipe and porous ceramic based sub wet-bulb temperature evaporative cooler: a theoretical and experimental study - Amer, Omar (2017)
Worldwide energy demand in buildings represents about 40-50% of the total energy consumption. In hot climates, such as Middle East and North Africa (MENA) countries, about 30% of the national power demand is used for HVAC applications in buildings. This has led to escalation in power demand in buildings for indoor air-cooling and high energy bills. This is exacerbated further by the widespread adoption of energy intensive and commercially dominant vapour compression air conditioning systems as the technology of choice.